Answer:
20
Step-by-step explanation:
Just write down the answer.
Answer: -1
Step-by-step explanation: plug in 25 into (-1)^n
Answer:
The answer is ![6x^{3} +39x^{2}+54x](https://tex.z-dn.net/?f=6x%5E%7B3%7D%20%2B39x%5E%7B2%7D%2B54x)
Step-by-step explanation:
Volume of the rectangular prism = Length * Width * Height
Length (l) = ![x+2](https://tex.z-dn.net/?f=x%2B2)
Width (w) = ![3x](https://tex.z-dn.net/?f=3x)
Height (h) = ![2x+9](https://tex.z-dn.net/?f=2x%2B9)
By substituting these values to the equation above,
Volume of the rectangular prism = ![(x+2)*3x*(2x+9)](https://tex.z-dn.net/?f=%28x%2B2%29%2A3x%2A%282x%2B9%29)
=![(3x^{2} +6x)*(2x+9)](https://tex.z-dn.net/?f=%283x%5E%7B2%7D%20%2B6x%29%2A%282x%2B9%29)
=![6x^{3} +27x^{2} +12x^{2} +54x](https://tex.z-dn.net/?f=6x%5E%7B3%7D%20%2B27x%5E%7B2%7D%20%2B12x%5E%7B2%7D%20%2B54x)
=![6x^{3} +39x^{2}+54x](https://tex.z-dn.net/?f=6x%5E%7B3%7D%20%2B39x%5E%7B2%7D%2B54x)
Therefore,
The answer is ![6x^{3} +39x^{2}+54x](https://tex.z-dn.net/?f=6x%5E%7B3%7D%20%2B39x%5E%7B2%7D%2B54x)
I believe you are correct keep it up